From the Cradle to the Grave: The Role of Macrophages in Erythropoiesis and Erythrophagocytosis - Klei, Thomas R. L.; Meinderts, Sanne M.; van den Berg, Timo K.; van Bruggen, Robin (Frontiers in Immunology, 2017)
Erythropoiesis is a highly regulated process where sequential events ensure the proper differentiation of hematopoietic stem cells (HSCs) into, ultimately, red blood cells (RBCs). Macrophages in the bone marrow play an important role in hematopoiesis by providing signals that induce differentiation and proliferation of the earliest committed erythroid progenitors. Subsequent differentiation towards the erythroblast stage is accompanied by the formation of so-called erythroblastic islands where a central macrophage provides further cues to induce erythroblast differentiation, expansion and hemoglobinization. Finally, erythroblasts extrude their nuclei which are phagocytosed by macrophages whereas the reticulocytes are released into the circulation. While in circulation, RBCs slowly accumulate damage which is repaired by macrophages of the spleen. Finally, after 120 days of circulation, senescent RBCs are removed from the circulation by splenic and liver macrophages. Macrophages are thus important for RBCs throughout their lifespan. Finally, in a range of diseases the delicate interplay between macrophages and both developing and mature RBCs is disturbed. Here we review the current knowledge on the contribution of macrophages to erythropoiesis and erythrophagocytosis in health and disease.